Unequal Inclusion: The Production of Social Differences in Education Systems - Marcus Emmerich; Ulrike Hormel (Social Inclusion, 2021)
The article raises the question of whether and how education systems produce social differences internally rather than reproducing pre‐existing “external” inequalities. Linking Niklas Luhmann’s theory of inclusion/exclusion with Charles Tilly’s theory of categorical inequalities, and based on empirical data from various qualitative studies, the article identifies an “observation regime” epistemically constituting the social classification of students and legitimising organisational closure mechanisms in the school system. As an alternative to the “reproduction paradigm,” a research approach guided by differentiation theory is proposed that takes into account that educational inequality operationally arises on the “inside” of the educational system and is caused by unequal inclusion processes.